Effect of Food Waste Digestate, Bokashi, and Cow Dung Fertilizer on Soil Chemical Properties and Growth Performance of Pak Choi (Brassica rapa subsp. chinensis) - Afrina Safawati Asri; 'Aisyah Mohamed Rehan (Progress in Engineering Application and Technology, 2026)
The misuse of chemical fertilizer has been deteriorating our soil and contaminating the environment. This study investigated the impact of cow dung fertilizer, bokashi fertilizer, and food waste digestate on the pH, electrical conductivity (EC), total carbon (TC), total nitrogen (TN), and crop growth of Pak choi (Brassica rapa subsp. chinensis). The controlled pot experiment was conducted at Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh Campus. Organic fertilizers were self-prepared and mixed with the soil before seed planting. Analysis of TC and TN of the soils was conducted on Day 0 and Day 28, while pH and EC analyses of the soils were conducted on five-day intervals i.e. 0, 7, 14, 21 and 28 days. Plant parameters measured were the height of plants and the width of leaves. Data was analyzed using one-way ANOVA. The highest plant height (11.0 cm) and maximum leaf widths (11.0 cm) were grown on soils fertilized with cow dung fertilizer. This is due to the high mineralization rate; however, the soil TC is decreased. The largest TC and TN increments (2.8595% and 0.1163%, respectively) were observed from bokashi fertilizer, indicating its great potential for sustained soil improvement, despite slow growth in plants at the initial state. Food waste digestates allowed intermediate plant growth and raised the soil pH to a slight alkaline of 7.20. In summary, cow dung fertilizer works best for short-term crop productivity and bokashi fertilizer for long-term carbon and nitrogen retention, while food waste digestates act as a balanced fertilizer. Long-term field tests for crop stability and overall improvement of soil quality should be done in future research.